2007
DOI: 10.1111/j.1939-1676.2007.tb01959.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of COAP and UW‐19 Protocols for Dogs with Multicentric Lymphoma

Abstract: Use of a long-term doxorubicin-containing sequential combination chemotherapy protocol is associated with a decreased risk of relapse and death relative to a non-doxorubicin-containing protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
73
0
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 25 publications
8
73
0
8
Order By: Relevance
“…Três cães encontravam-se no estágio IV, ou seja, envolvimento de fígado e/ou baço com ou sem o estágio III, (16,67%), dois no estágio II, envolvimento de múltiplos linfonodos regionais, (11,11%), um no estágio III, linfadenopatia generalizada, (5,55%) e um no estágio I, envolvimento de apenas um linfonodo, (5,55%). Doze animais apresentaram-se no sub-estágio "b" (presença de sinais sistêmicos) (66,7%) e seis no sub-estágio "a" (ausência de sinais sistêmicos) (33,3%), diferentemente do que relata a literatura internacional, já que a maioria dos autores afirma que a maior parte dos cães com linfoma não apresenta sinais sistêmicos da doença no momento do diagnóstico (HOSOYA et al, 2007;VAIL & YOUNG, 2007).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Três cães encontravam-se no estágio IV, ou seja, envolvimento de fígado e/ou baço com ou sem o estágio III, (16,67%), dois no estágio II, envolvimento de múltiplos linfonodos regionais, (11,11%), um no estágio III, linfadenopatia generalizada, (5,55%) e um no estágio I, envolvimento de apenas um linfonodo, (5,55%). Doze animais apresentaram-se no sub-estágio "b" (presença de sinais sistêmicos) (66,7%) e seis no sub-estágio "a" (ausência de sinais sistêmicos) (33,3%), diferentemente do que relata a literatura internacional, já que a maioria dos autores afirma que a maior parte dos cães com linfoma não apresenta sinais sistêmicos da doença no momento do diagnóstico (HOSOYA et al, 2007;VAIL & YOUNG, 2007).…”
Section: Resultsunclassified
“…Dos cães que atingiram RC, três morreram em 56 a 180 dias após o início do tratamento. Dessa forma, 18 animais iniciaram o protocolo de quimioterapia e, em 180 dias após o início do tratamento, (HOSOYA et al, 2007). Tal protocolo passou por modificações, principalmente com relação à sua duração, desde que foi primeiramente publicado por KELLER et al (1993).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Dogs were subjected to the adapted 19-week Madison-Wisconsin chemotherapy protocol (UW-19) (Hosoya et al, 2007;Chun et al, 2009). Leucocyte separation for flow cytometry was only repeated in the LG after the 5 th week of treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Various CHOP-based protocols were published following these decades, all consisting of a CHOP-based induction phase, again followed by a prolonged maintenance phase (Teske and others 1990, Stone and others 1991, Keller and others 1993, Myers and others 1997, Zemann and others 1998, Kessler and Kandel 2004, Siedlecki and others 2006, Simon and others 2008, Daters and others 2010). Over the past 15 years, various studies have suggested that discontinuous polychemotherapy protocols ranging from 12 to 26 weeks total duration without a maintenance phase are equally or even more effective than the older continuous protocols with maintenance therapy (Chun and others 2000, Moore and others 2001, Garrett and others 2002, MacDonald and others 2005, Simon and others 2006, Hosoya and others 2007, Rassnick and others 2010, Simon 2010, Sorenmo and others 2010). However, this observation is based on relatively small numbers of dogs (n=24–130).…”
mentioning
confidence: 99%